Recent Developments in Extracellular Matrix Remodeling for Fat Grafting - Bi, Xin; Li, Ye; Dong, Ziqing; Zhao, Jing; Wu, Weizi; Zou, Jialiang; Guo, Lingling; Lu, Feng; Gao, Jianhua (Frontiers in Cell and Developmental Biology, 2021)
Remodeling of the extracellular matrix (ECM), which provides structural and biochemical support for surrounding cells, is vital for adipose tissue regeneration after autologous fat grafting. Rapid and high-quality ECM remodeling can improve the retention rate after fat grafting by promoting neovascularization, regulating stem cells differentiation, and suppressing chronic inflammation. The degradation and deposition of ECM are regulated by various factors, including hypoxia, blood supply, inflammation, and stem cells. By contrast, ECM remodeling alters these regulatory factors, resulting in a dynamic relationship between them. Although researchers have attempted to identify the cellular sources of factors associated with tissue regeneration and regulation of the microenvironment, the factors and mechanisms that affect adipose tissue ECM remodeling remain incompletely understood. This review describes the process of adipose ECM remodeling after grafting and summarizes the factors that affect ECM reconstruction. Also, this review provides an overview of the clinical methods to avoid poor ECM remodeling. These findings may provide new ideas for improving the retention of adipose tissue after fat transplantation.